Recht und Auslegung bei Bernhard Windscheid - Korn, Kamil (Z Dziejów Prawa [czasopismo zamknięte], 2020)
The subject of the following article is the views of German jurist Bernhard Windsc- heid on law and its interpretation. Bernhard Windscheid is traditionally regarded as a prominent representative of pandectists, conceptual jurisprudence, and legal positivism. In legal historiogra- phy an opinion about an excessive formalism and detachment from reality in his studies was held for a long time and is still partially maintained. In most recent studies, however, that assessment has been revised, and a more diversified picture of Windscheid has emerged of a scholar who is hard to define by means of simple formulas. The analysis of his views on law and its interpretation conducted in this article leads to the conclusion that the traditional picture of Windscheid as a representative of „bloodless conceptual jurisprudence” is incorrect. According to Windscheid, the aim of the interpretation of law is to find out the legislator’s intention and realize it accordingly, which however, does not exclude taking into consideration under some circumstances the requirements of legal relations and transactions with values such as righteousness. In Windsc- heid’s concept, limits of the interpretation of law are drawn quite broadly, although he simulta- neously attempts to specify them clearly enough to prevent freedom of interpretation and not to jeopardize the certainty of law.